Employability of fresh graduates as skilled labour in the construction industry at Perak Tengah - Mohd Zarni, Putera Danish Zakwan; Aziz, Nor Diana; Nur Farrahayu Edora, Rohaizat; Omardin, Mohammad Affendy; Hasan, Ramly (2024)
Labour shortage in Malaysia is becoming critical, especially for fresh graduates. The unemployment of fresh graduates seeking to work as skilled labour in the construction industry has been a topic of discussion and debate over the past few years. There is a search for ideal solutions to overcome this issue. Some studies claim that the main reason for the unemployment of fresh graduates is the influx and domination of foreign labour. This study aims to find out possible factors that impact the employability of fresh graduates in the construction industry. A qualitative approach, involving a semi-structured interview, was selected. Six participants were chosen from the professional government sector, including assistant engineers, among others. From this study, three factors were identified- fresh graduates have issues with soft skill competencies; the foreign labour force dominates the construction industry, leading to discouragement for fresh graduates to work as skilled labour; and labour benefits are limited, discouraging fresh graduates from pursuing skilled labour positions. Some factors need to change for several reasons. For instance, fresh graduates have many options, and the government offers lower allowances than private companies. Lastly, some factors need to be removed due to various reasons. These factors include the poor image of working in construction, the need to improve the working environment in the construction industry, and the lack of safety and security in the construction sector.